2020
DOI: 10.3390/s20102908
|View full text |Cite
|
Sign up to set email alerts
|

A Flexible and Low-Cost Tactile Sensor Produced by Screen Printing of Carbon Black/PVA Composite on Cellulose Paper

Abstract: This study presents the design and fabrication of a flexible tactile sensor printed on a cellulose paper substrate using a carbon black (CB) – filled polyvinyl alcohol (PVA) polymer matrix as ink material. In the design, electrodes are obtained by screen printing of CB/PVA composite on dielectric cellulose paper. The screen-printing method is preferred for fabrication because of its simplicity and low manufacturing cost. The tactile sensor is formed by overlapping two ink-printed sheets. Electrical properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…In addition to resistive sensing applications, [86,87,104,105] cellulose-added flexible electronics studies involving the impedance concept in which multiple electrical characteristics are examined have also gained momentum. [51,95,106] As the scanning electron microscopy (SEM) and atomic force microscopy (AFM) images reported in these studies are examined, it can be observed that the sponge-like structures create a microcapacitive effect in the cellulose structure. The amount of coated conductive material adjusts the resistance.…”
Section: Cellulose and Derivativesmentioning
confidence: 99%
“…In addition to resistive sensing applications, [86,87,104,105] cellulose-added flexible electronics studies involving the impedance concept in which multiple electrical characteristics are examined have also gained momentum. [51,95,106] As the scanning electron microscopy (SEM) and atomic force microscopy (AFM) images reported in these studies are examined, it can be observed that the sponge-like structures create a microcapacitive effect in the cellulose structure. The amount of coated conductive material adjusts the resistance.…”
Section: Cellulose and Derivativesmentioning
confidence: 99%
“…[ 22 ] On a capacitive touch sensor, the electrode line width should be optimized compromising lower line width while maintaining high conductivity to have a fast signal propagation. [ 23 ] Therefore, the rheology of the ink must be tuned as well as selecting a screen‐printing stencil with a high mesh count that allows high‐resolution patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Handwriting, using pencils [ 32–34 ] or ink pens, [ 35–40 ] is a simple, fast, low‐cost, and graphical method to create circuits on paper. Costa et al.…”
Section: Introductionmentioning
confidence: 99%